Self-directed learning strategies in adult educational contexts - Giuseffi, Francesco G., 1972- (IGI Global, 2019)
"This book examines how self-directed learning methods and strategies is impacting adult learning in various formal and informal learning situations and educational encounters. It also explores theories and research-based learning strategies that are self-directed in nature and to find connections to enhance various connections to adult learning"--
Keywords: vzdělávání dospělých; sebevzdělávání; autoregulace učení; adult learning; self-regulated learning; self-education; sborníky; papers of several authors